Rancang Bangun Sistem Pengontrolan Arus Dan Temperatur Pada Kompor Listrik Berbahan Bakar Air Berbasis Arduino MEGA 2560 - Nasrul Nasrul; Witrionanda Witrionanda (Jurnal Teknik Elektro, 2019)
Water stove is one type of development in the field of alternative energy by utilizing a water electrolysis process that separates water molecules into hydrogen and oxygen gas by flowing electric current into electrolytes (water fluid and NaCl catalyst) through Aluminum electrodes. Hydrogen and oxygen gas are used as fuel for water stoves to light a fire. Electrolyser is designed by using 4 tubes with maximum fluid per tube consisting of 250 mL water and 4 gram NaCl catalyst. The stability of the electrolysis process is regulated based on current flow and temperature in the process. Monitoring current using ACS712 current sensor and temperature control using a thermistor that is used as temperature control at the temperature of the tube area and then processed by the Arduino mega 2560 microcontroller. In the electrolyzer with a 12 Volt 21 A voltage source, the water stove can light a fire with a maximum current of 21 A (2 tubes in parallel with a maximum current of 10.5 A) and a temperature setpoint of 700 C. However, the current is too large and the temperature too high can cause heat and increase the electrolyzer chamber temperature and this negatively impacts the electrolyzer tube. Based on this explanation, a regulatory unit is needed in the form of current and temperature controls on the electrolyzer to prevent excessive evaporation of the tube and make the tube too hot and melt. With the current and temperature control and proper construction, the water stove is safer when operated by the user.